2022
DOI: 10.1097/md.0000000000030516
|View full text |Cite
|
Sign up to set email alerts
|

The influence of marital status on survival in patients with nasopharyngeal carcinoma: A surveillance, epidemiology, and end results database analysis

Abstract: Background: To assess the influence of marital status on the survival of patients with nasopharyngeal carcinoma (NPC), we used the Surveillance, Epidemiology, and End Results (SEER) database to analyze 5477 patients who were diagnosed with NPC from 2004 to 2016.Methods: Kaplan-Meier survival analysis and Cox proportional hazard regression were used to analyze the influence of marital status on cause-specific survival (CSS) and overall survival (OS). Subgroup analyses was used to assess the influence of marital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Furthermore, marital status has been associated with disparities in early cancer diagnoses ( 33 ). Previous results suggested that married patients are more likely to receive earlier clinical diagnoses, which generally correspond to better prognoses ( 34 , 35 ), whereas unmarried patients often face delays in diagnosis and may not receive adequate treatment ( 36 ). These factors highlight the potential role of maintaining a good marital relationship can therefore improve the prognosis of patients with NECB.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, marital status has been associated with disparities in early cancer diagnoses ( 33 ). Previous results suggested that married patients are more likely to receive earlier clinical diagnoses, which generally correspond to better prognoses ( 34 , 35 ), whereas unmarried patients often face delays in diagnosis and may not receive adequate treatment ( 36 ). These factors highlight the potential role of maintaining a good marital relationship can therefore improve the prognosis of patients with NECB.…”
Section: Discussionmentioning
confidence: 99%
“…The time of index date was the date one year after the NPC diagnosis. To make the general condition of our study population more homogenous, the following exclusion criteria were obeyed to discard patients with extreme morbidity: (1) age younger than 20 years old, (2) blindness before the index date, (3) the diagnosis of ocular tumor before index date, (4) the receipt of eyeball removal before the index date, (5) the receipt of corneal transplantation before the index date, (6) achievement of outcome before index date, (7) died before index date. After the exclusion process, we performed two matching processes for the constitution of NPC and non-NPC groups.…”
Section: Patient Selectionmentioning
confidence: 99%
“…The Epstein-Barr virus, human papillomavirus, and tobacco smoking were shown to be causally linked to the development of NPC [1,3,4]. Currently, the main treatments for NPC are radiotherapy and chemotherapy, with a recurrence rate of approximately 10-20 percent [5,6], and the median of survival period is 3 years in the advanced stage, which could be influenced by marital status [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The choices of treatments for the NPC involve chemotherapy and radiotherapy and the recurrence of NPC is not uncommon [5,6]. The mean survival interval of late-stage NPC patients were near 3 years which could be further shortened if the patient was under the divorce status [7,8].…”
Section: Introductionmentioning
confidence: 99%